Biopolymers Carrying Essential Oils, or their Compounds, for Food Antimicrobial Packaging - Requena, Raquel; Vargas, Maria; Atares, Lorena; Chiralt, Amparo (Current Organic Chemistry, 2018)
Background: Biodegradable antimicrobial materials for food packaging applications are in great demand by the food industry and society alike for the purposes of extending food shelf life, thus reducing the environmental impacts associated with synthetic plastics. Among the natural and non-toxic active compounds available, essential oils and their major components have been widely studied due to their antioxidant and antimicrobial properties together with their Generally Recognized as Safe status. Objective: In this review, the antimicrobial and antioxidant properties of several essential oils and their major compounds are summarized, as well as their action when included in different biopolymer-based matrices. Both the method of incorporating active ingredients into the biopolymer matrix and the yield of such processes as a function of the technique used (casting methods or thermoplastic processing) are also assessed. The effect of active compounds on the functional properties of the films is reviewed, as well as the effective release of the active ingredients into different food systems and food simulants, as affected by polymer-active interactions and the nature of the food. Conclusion: Finally, the antimicrobial action of some of these active compounds (embedded in different biopolymer matrices) is also discussed both in in vitro studies and in antimicrobial tests performed using foods of different compositions.
Keywords: Biopolymer